Mapeamento da gestão do conhecimento por meio das ferramentas da gestão da qualidade em micro e pequenas empresas - Bastiani, Jeison Arenhart de (2013)
Nowadays Brazil is the country with the most of ISO 9001 certified companies in Latin America. Quality management processes and continuous improvements methods like PDCA are present in these companies and are widely used on management systems. The smallest companies are really important on this background, once they are 99% of the total brazilian companies. With the upcoming knowledge management as a strategy for competition, just like the quality management systems, this work has showed how the knowledge management happens on these small companies inside the continuous improvement activities (PDCA / MASP). The subject of this thesis was the start of a quality management process in a small company, where we’ve seen the knowledge management critical points when creating the management system documentation. Also was evaluated the quality management and the software tools used and its contributions to knowledge management.